2021
DOI: 10.1002/cbdv.202001065
|View full text |Cite
|
Sign up to set email alerts
|

(+/−)‐Alashanoid N, Two Enantiomeric Sesquiterpenes from Syringa pinnatifolia

Abstract: Two enantiomeric humulane sesquiterpenes, namely (+)‐alashanoid N (1a) and (−)‐alashanoid N (1b), along with two known analogs ((2R,3R,5R)‐2,3‐epoxy‐6,9‐humuladien‐5‐ol‐8‐one (2) and (2R,3S,5R)‐2,3‐epoxy‐6,9‐humuladien‐5‐ol‐8‐one (3)), were described from the peeled stems of a folk Mongolian herbal medicine Syringa pinnatifolia. Their structures were characterized based on UV, IR, NMR, and HR‐ESI‐MS data analyses, and the absolute configurations were determined by data analysis of X‐ray diffraction and quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…According to recent studies, many new sesquiterpenes and lignans have been identified in S. pinnatifolia [ 8 , 39 , 40 ]. Therefore, this woody plant is a valuable resource for discovering new compounds, especially sesquiterpenes and lignans, which may be regarded as potentially important chemicals in the development of medicines because of their abundance in S. pinnatifolia [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, many new sesquiterpenes and lignans have been identified in S. pinnatifolia [ 8 , 39 , 40 ]. Therefore, this woody plant is a valuable resource for discovering new compounds, especially sesquiterpenes and lignans, which may be regarded as potentially important chemicals in the development of medicines because of their abundance in S. pinnatifolia [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were a few eremophilane dimers reported from several genera such as Ligularia, [18 -20] Incarvillea, [21] and Eremophila, [22] but none has been described in Oleaceae except for syringenes AÀ L from SP. [15] Therefore, compared to humulane such as zerumbone, and alashanoids AÀ S, [9,11,12,14] dimeric eremophilane might serve as a more characteristic chemical marker to distinguish SP from other Syringa species, which provides another chemical evidence to support the classification controversy for previous methods. [23]…”
Section: Resultsmentioning
confidence: 99%
“…The extraction and fractionation procedures were previously reported [12] . Briefly, the powdered and air‐dried peeled stems (20 kg) of S. pinnatifolia were extracted with EtOH under reflux with 95 % and 80 % (25 L, each 1.5 h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our group reported a series of sesquiterpenoids with diverse types from SP, such as humulane, caryophyllane, eremophilane, and recent discovered syringane and pinnatane, [7–11] and found that many sesquiterpenoids from SP exit as racemates, which provided inspiration for the potential unusual biosynthesis of sesquiterpenoids within this species. In order to discover new and more biological sesquiterpenoids, a continued phytochemical investigation was performed on the terpenoid‐enriched portion, guided by 1 H‐NMR spectroscopic data of SP fractions, which led to the isolation of five new sesquiterpenoids ( Figure 1), namely alashanoids O–S ( 1 – 5 ), including two seco‐humulanes with a rare 13‐membered oxygen heterocycle framework and three eremophilane ones, along with three known analogs ( 6 – 8 ).…”
Section: Introductionmentioning
confidence: 94%